Future of Currency: Crypto - Mayuri Gosai; Monil Kotadia; Jignesh Vidani (International Journal of Applied and Scientific Research, 2024)
The rise of cryptocurrencies is transforming the global currency landscape, offering an alternative to traditional money. Digital currencies like Bitcoin and Ethereum are revolutionizing financial transactions with decentralization, transparency, and security. This research explores the potential of cryptocurrencies to disrupt the financial system, particularly in banking, payment processing, and financial inclusion. Using a mixed-methods approach, combining qualitative and quantitative data, this study provides a comprehensive view of the opportunities and challenges of cryptocurrencies. Unlike other research, this study focuses on the intersection of cryptocurrency adoption and financial inclusion, and incorporates expert interviews and case studies to provide a nuanced understanding of the complex relationships between cryptocurrencies and traditional financial systems